1991
DOI: 10.1002/jez.1402600111
|View full text |Cite
|
Sign up to set email alerts
|

Defensive function of trichocysts in Paramecium

Abstract: A putative defensive function of trichocysts in Paramecium has been tested experimentally. Cells of trichocyst-non-discharge (tnd) mutant, artificially induced trichocyst-deficient cells, and intact wild-type cells were compared as prey for a carnivorous ciliate, Dileptus margaritifer. Cells of tnd mutants were eaten 9-45 times faster than wild-type cells by the predator in P. caudatum and P. tetraurelia. Encounters between paramecia and dilepti occurred in nearly the same frequency in mutant and wild-type cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 17 publications
2
64
0
Order By: Relevance
“…In a more complicated situation, when a Paramecium cell meets a predatory organism, the first reaction is expulsion of elongate trichocysts to keep the predator at a distance, as first shown by Harumoto and Miyake [76] and in more detail by Knoll et al [44]. The concept of a defensive function of trichocyst expulsion [76] can be supplemented by the observation that this is followed with little delay by ciliary reversal [44].…”
Section: Functional Aspects Of Ciliary Reversalmentioning
confidence: 98%
“…In a more complicated situation, when a Paramecium cell meets a predatory organism, the first reaction is expulsion of elongate trichocysts to keep the predator at a distance, as first shown by Harumoto and Miyake [76] and in more detail by Knoll et al [44]. The concept of a defensive function of trichocyst expulsion [76] can be supplemented by the observation that this is followed with little delay by ciliary reversal [44].…”
Section: Functional Aspects Of Ciliary Reversalmentioning
confidence: 98%
“…Surprisingly, comparison of time constants shows that Paramecium can operate its stimu-lated exo-endocytotic system faster than any other dense-core-vesicle system. This may be vital for the cell, enabling it to use trichocyst exocytosis for defense against a predator, as first shown by Harumoto and Miyake (1991). Locally released trichocysts may act as a spacer to ward off the attacker, while the cell switches to "back gear" by subsequent ciliary reversal and, thus, escapes with very high efficiency (Knoll et aL., 1991b).…”
Section: E Stimulated Exocytosis and Endocytosismentioning
confidence: 98%
“…special organelles that extrude explosively in response to mechanical or chemical stimuli. Haramuto & Miyake (1991) have demonstrated that Paramecium trichocysts ensure effective defence against a predatory ciliate Dileptus margaritifer. Recently, Buonanno et al (2013) provided evidence that trichocysts of Paramecium tetraurelia were also efficient against some metazoan predators such as the rotifer Cephalodella sp.…”
Section: Discussionmentioning
confidence: 99%